Synthesis of a Cyclic Analogue of Tuv N-Methyl Tubulysin - Park, Yunjeong; Lee, Jae Kyun; Ryu, Jae-Sang (Synlett, 2015)
Tubulysins are the most potent antimitotic agents known so far. We are interested in the conformational effect of tubulysin and herein we report the design and synthesis of a conformationally rigid cyclic analogue of Tuv N-methyl tubulysin. A conformationally rigid tetrahydropyran moiety was incorporated into the Tuv fragment via enantioselective hetero Diels–Alder reaction to prevent the rotation of the Tuv chain. The following diastereoselective reductive amination yielded the (4-methylamino)tetrahydropyranyl Tuv fragment, which was coupled to d-Mep-l-Ile dipeptide fragment and Tup fragment sequentially.
Keywords: antitumor agents; peptides; Diels–Alder reaction; asymmetric catalysis; medicinal chemistry; asymmetric synthesis